Low serum uric acid levels in progressive supranuclear palsy. Issue 3 (21st December 2015) - Oropesa‐Ruiz, Juan Manuel; Huertas‐Fernández, Ismael; Jesús, Silvia; Cáceres‐Redondo, María Teresa; Vargas‐Gonzalez, Laura; Carrillo, Fátima; Carballo, Manuel; Gómez‐Garre, Pilar; Mir, Pablo
ABSTRACT: Introduction: Uric acid is a natural antioxidant, and it has been shown that low levels of uric acid could be a risk factor for the development of PD. Our aim was to investigate whether uric acid plays a role in PSP. Methods: We carried out a cross‐sectional study to compare serum uric acid levels between PSP patients, PD patients, and healthy controls. We also analyzed longitudinal uric acid levels in the PSP group. Results: PSP patients showed reduced levels of serum uric acid as compared to healthy controls. This reduction was similar to that found in patients with PD. Uric acid levels of PSP patients did not change with time. Conclusion: Serum uric acid levels are reduced in PSP as well as in PD compared to healthy controls. Our data suggest that high levels of uric acid could be a natural protective factor against PSP. © 2015 International Parkinson and Movement Disorder Society